PHYTOCHEMICAL STUDY OF ZYGOPHYLLUM ALBUM EXTRACT - A, Belmimoun; B, Meddah; Larbi K, Side; P., Sonnet (International Journal of Engineering Technologies and Management Research, 2017)
The aerial parts of Zygophyllum album L. are used in folk medicine as an anti-diabetic agent and as a drug active against several pathologies. In this work we present the chemical composition of Algerian phenolic extracts obtained by different solvents and extraction methods The phytochemical study was based on a colometer method, Phenolic compound content and LC/ESI-MS analyses The methanolic extract of zygophyllum album was at least the best extract studied for its quantitative and qualitative richness in phenolic compounds All Z.album extracts and specially the methanolic one are a promising source of health products for functional food or nutraceutical industries.